An investigation into the benefits and risks of the integration and application of Reclaimed Asphalt (RA) and Warm Mix Asphalt (WMA) technology into the South African asphalt industry - Stander, A. H. (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScEng)--Stellenbosch University, 2014.